IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY AND GOOD CORPORATE GOVERNANCE ON FIRM VALUES IN THE MINING SECTOR - Tamara, I Gusti Ayu Agung Tia Permata; Pertiwi, I Dewa Ayu Eka; Kristiantari, I Dewa Ayu (Accounting Study Program, Universitas Ciputra Surabaya, 2024)
The objective of this research is to investigate the effects of the mining industry's adoption of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR), as represented by the audit committees, independentcommissioners, and board of directors, on company value. The study's secondary data sources were the annual reports and sustainability reports of mining businesses that were listed between 2018 and 2020 on the Indonesia Stock Exchange. Ten mining industry enterprises made up the sample, which was chosen using purposive sampling. Multiple linear regression analysis was employed to test the sample. The study's findings show that implementing CSR significantly and favourably affects a company's value. On the other hand, the application of GCG through the proxy of the board of directors has an insignificant and negative impact on firm value, independent commissioners have a large and positive impact on firm value, and audit committees have a positive and insignificant impact on firm value.